Adaptive Artificial Passive Immunity as a Suggested Strategy for Treatment of COVID-19 Critical Cases - Ahmed, G. Elkabily; Mahmoud, M. Sebaiy (Journal of Current Viruses and Treatment Methodologies, 2020)
Currently, the emergence of a novel human corona virus, SARS-CoV-2, has become a global health concern causing severe respiratory tract infections in humans. Human-to-human transmissions have been described with incubation times between 2-14 days, facilitating its spread via droplets, contaminated hands or surfaces, resulting in high spread and death rates according to date, time and place of infection. We therefore reviewed the literature on all available information about the treatment of the cases, especially critical cases to decrease the mortality rate, the spread and incubation time of the virus by using the adaptive artificial passive immunity (anti-bodies from fully recovered patients with COVID-19).
Keywords: Coronavirus; 2019-nCoV; Covid-19; Epitope; B cell; vaccine